Space and Sonship: Paul’s Familial Metaphors in Rom 8 - Potgieter, Annette (Religions, 2024)
Paul often uses metaphors as a method of persuasion. In Rom 8, Paul’s use of kinship metaphors such as “sonship” and being “heirs” is particularly ubiquitous. Paul writes to an audience situated in Rome where they would have been well aware of kinship metaphors as this inter alia formed part of the Julio-Claudio Caesars’ vocabulary and legitimation of their rule. Paul’s familial metaphors would have resonated with an audience in Rome au fait with the notion of adoption and its implications. The use of the images of “sonship” and “heir” also function as spatial metaphors indicating a vertical and horizontal understanding which the audience would have picked up on. The spatial metaphors contribute to an understanding of “in” and “out”, underscoring an alternative family identity found in Christ. These metaphors play a role in the formation and construction of what is later to be called early Christianity.